2012
DOI: 10.1590/s0104-11692012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care time in the Intensive Care Unit: evaluation of the parameters proposed in COFEN Resolution Nº 293/04

Abstract: Tiempo de asistencia de enfermería en la Unidad de CuidadosIntensivos: evaluación de los parámetros propuestos por la Resolución COFEN nº 293/04Este estudio tuvo como objetivo evaluar los parámetros establecidos por la Resolución COFEN 293/04, referencia para dimensionamiento de personal de enfermería en unidades de cuidados intensivos adultos (UCIA). La investigación se realizó en seis hospitales de la ciudad de São Paulo. La cantidad media diaria de profesionales necesarios para la asistencia al paciente se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
1
10
2
13
Order By: Relevance
“…(7) Regarding the Braden scale, the mean risk score found was similar to other researches that found scores ranging from 12.1 to 14.9. (13,17) The occurrence of PS, even though it was the most frequent AE found in this study, similar to another Brazilian study, (7) can be considered low compared to other studies. These studies addressed factors associated to the development of PS in patients hospitalized in ICU, and found higher age mean, longer hospitalization time, a lower Braden score and higher clinical severity in the group of patients that developed sores.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…(7) Regarding the Braden scale, the mean risk score found was similar to other researches that found scores ranging from 12.1 to 14.9. (13,17) The occurrence of PS, even though it was the most frequent AE found in this study, similar to another Brazilian study, (7) can be considered low compared to other studies. These studies addressed factors associated to the development of PS in patients hospitalized in ICU, and found higher age mean, longer hospitalization time, a lower Braden score and higher clinical severity in the group of patients that developed sores.…”
Section: Discussionsupporting
confidence: 85%
“…These studies addressed factors associated to the development of PS in patients hospitalized in ICU, and found higher age mean, longer hospitalization time, a lower Braden score and higher clinical severity in the group of patients that developed sores. (13,17) There was only one case of fall in this study, a rate much lower than the ones found in other studies that also addressed this event. (6,8) This study has some limitations, mostly regarding the low risk profile of the patients admitted in the ICU studied.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Faced with this scenario, the management responsible for quantifying nursing professionals for safe patient care and managing the human resources under their responsibility needs instruments, such as the Patient Classification System (PCS) (3) , to help in the planning, allocation, distribution, and control of the workforce, one of the most significant determinants of hospital effectiveness, quality, and cost.…”
Section: Introductionmentioning
confidence: 99%